Pembangunan Berkelanjutan Melalui Badan Usaha Milik Desa : (Studi Kasus BUMDes Ketapanrame, Kecamatan Trawas, Kabupaten Mojokerto Jawa Timur) - Alif Muzhaqi (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The presence of village Sustainable Development Goals and village-owned enterprises is crucial to the development of regional economic activities and development as well as a major part of enabling the region to open up decent employment opportunities. The position of BUMDesa and the Sustainable Development Goals program has been regulated in legislation and local government policies. This research is descriptive research using a qualitative approach, namely a study by describing the data that researchers have collected, both data from interviews, observation and documentation during the research. Data analysis techniques used in qualitative research include transcripts of interview results, data reduction, data presentation and conclusion drawing. The results of data processing show that Ketapanrame Village has realized a sustainable development program through BUMDesa with 18 objectives of the village sustainable development program. The linkage shows such as the increasing welfare of the community, the lower unemployment rate because BUMDesa absorbs labor and partnerships almost entirely from the total number of villagers, the higher economy because almost all residents become BUMDesa partners. The level of village development is getting higher but the local government still maintains green land for food security and greening. Need for transparency of BUMDesa programs so that every citizen knows and understands entirely. Human Resources also need continuous coaching.